2014
DOI: 10.1088/0957-0233/26/1/015305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EIT systems and algorithms for handling full void fraction range in two-phase flow measurement

Abstract: Abstract:In the aqueous-based two-phase flow, if the void fraction of dispersed phase exceeds 0.25, the conventional Electrical Impedance Tomography (EIT) produces a considerable error due to the linear approximation of Sensitivity Back-projection method, which limits the EIT's wider application in process industry. In this paper, an EIT sensing system which is able to handle full void fraction range in two-phase flow is reported. This EIT system employs a voltage source, conducts true mutual impedance measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…computer is used to collect and store the data from the DAS system. After obtaining the voltage measurements from DAS system, the host computer processes the data by using modified sensitivity back projection image reconstruction algorithm [48]. The forward and inverse problems are used to analyze the reconstruction of conductivity distribution.…”
Section: Electrical Resistance Tomographymentioning
confidence: 99%
“…computer is used to collect and store the data from the DAS system. After obtaining the voltage measurements from DAS system, the host computer processes the data by using modified sensitivity back projection image reconstruction algorithm [48]. The forward and inverse problems are used to analyze the reconstruction of conductivity distribution.…”
Section: Electrical Resistance Tomographymentioning
confidence: 99%
“…The gas concentration set from WMS can be derived by [30] = 1 (19) where, is the local gas concentration (i.e. void fraction) at each crossing-point.…”
Section: Visualisation Of Large Bubble In Gas-water Flowmentioning
confidence: 99%
“…The recent research work found that based on the nonlinear approximation, the modified sensitivity backprojection (MSBP) method as expressed in Equation (3) (Wang, et al 1996, Wang 2002) is a more accurate approximation than the traditional linear back-projection method (Kotre, 1992) to obtain the k th conductivity ratio σ k /σ 1 (Jia, et al, 2015).…”
Section: Sensitivity Matrixmentioning
confidence: 99%
“…The Maxwell relationship (Maxwell 1873) formulated in Equation (4) with the zero conductivity of particles is mostly used to correlate the k th local gas volume fraction c k over pixel a k in gas-liquid flow from the corresponding local conductivity  k with the assumption of gas volumetric distribution in an element to be homogeneous. In addition, the applicability of Maxwell relationship to high volume fraction were reported (Holder et al 1998;Sharifi and Young, 2013;Jia et al, 2015) 1 1…”
Section: Correlation Between Conductivity and Volume Fractionmentioning
confidence: 99%